Microparticle‐associated tissue factor activity: a link between cancer and thrombosis? - TESSELAAR, M. E. T.; ROMIJN, F. P. H. T. M.; VAN DER LINDEN, I. K.; PRINS, F. A.; BERTINA, R. M.; OSANTO, S. (Journal of thrombosis and haemostasis, 2007)
Background: Cancer, in particular mucinous adenocarcinoma, is associated with venous thromboembolism (VTE). Tissue factor (TF), initiator of coagulation, plays a central role in the paradigm that clotting and tumor growth form a vicious circle, in which hypercoagulability facilitates the aggressive biology of cancer and vice versa. Expression of TF in tumors is associated with poor differentiation and poor prognosis. Patient/methods: We investigated the association between clinically manifest VTE and procoagulant properties of circulating microparticles (MP) isolated from blood of unselected pancreatic and breast adenocarcinoma patients' consecutive subjects, who presented with ultrasound or CT‐scan confirmed VTE, and healthy subjects. Results: Patients with disseminated breast and pancreatic cancer had significantly increased levels of MP‐associated TF activity compared with healthy controls, subjects with idiopathic acute VTE and non‐metastatic cancer patients. Patients with both high MP‐associated TF‐activity and MP‐associated epithelial mucin (MUC1) had a lower survival rate at 3–9 months follow‐up than those with low TF‐activity and no MUC1 expression: the likelihood of survival was 0.42 (95% CI: 0.19– 0.94) for an individual with these two predictor variables present, after adjustment for other factors (age cohort, type of cancer, VTE) in the Cox proportional hazards model. Conclusions: Our results suggest an important role for MP‐associated TF and MUC1 in the pathogenesis of thrombosis in disseminated mucinous adenocarcinoma patients. Future studies should reveal the mechanism underlying the observed associations.